RNA Interference-Induced Innate Immunity, Off-Target Effect, or Immune Adjuvant? - Meng, Zhongji; Lu, Mengji (Frontiers in Immunology, 2017)
RNA interference (RNAi) is a natural cellular mechanism that inhibits gene expression in a sequence-specific manner. In the last decade, RNAi has become a cornerstone in basic biological systems research and drug development efforts. The RNAi-based manipulation of mammalian cells facilitates target identification and validation; assists in identifying human disease etiologies; and expedites the development of treatments for infectious diseases, cancer, and other conditions. Several RNAi-based approaches are currently undergoing assessment in phase I and II clinical trials. However, RNAi-associated immune stimulation might act as a hurdle to safe and effective RNAi, particularly in clinical applications. The induction of innate immunity may originate from small interfering RNA sequence–dependent delivery vehicles and even the RNAi process itself. However, in the case of antagonistic cancers and viral infection, immune activation is beneficial; thus, immunostimulatory small interfering RNAs were designed to create bifunctional small molecules with RNAi and immunostimulatory activities. This review summarizes the research studies of RNAi-associated immune stimulation and the approaches for manipulating immunostimulatory activities.